Workplace Matters: The Use of Parental Leave Policy in Japan. (August 2015) - Mun, Eunmi; Brinton, Mary C.
Policies to render employment and family more compatible have been adopted in many postindustrial countries. But the organizational contexts that facilitate or hinder employees' policy usage have been underexamined. This article addresses this gap by analyzing the organizational conditions associated with greater use of parental leave policy in the workplace. The authors draw on organizational data from contemporary Japan, a setting that epitomizes norms of the ideal worker and intensive parenting that are increasingly highlighted in studies of work–family conflict in the United States. Analyzing panel data on more than 500 large Japanese companies from 2001 to 2009, the authors find greater utilization of parental leave policies in firms that have a higher representation of women in managerial positions and that include human resource executives on the corporate board. Usage does not increase, however, in firms that offer parental leave that is longer than legally mandated. These results highlight the importance of key features of the organizational context in enhancing employees' use of parental leave policy.